VD_FINDINFO Jug / 2022 / 474 vom 9. Juni 2022 - VD Tribunal cantonal (2022)
DROIT DE LA FONCTION PUBLIQUE, RÉPRIMANDE, EMPLOYÉ PUBLIC, PROPORTIONNALITÉ, DROIT D'ÊTRE ENTENDU, FAUTE | 53 CO, 29 al. 2 Cst., 50 LPers-VD, 59 LPers-VD, 124 RLPers-VD, 135 RLPers-VD, 136 RLPers-VD, 137 RLPers-VD